The Sacred, Nature, and Technology - Cruz, Eduardo R. (Zygon, 2006)
Abstract. Bronislaw Szerszynski's Nature, Technology and the Sacred prompts a short reflection on the meaning of “the sacred.” Although it is part of the main thread of the book, the description of traditional and modern sacred does not seem to take into account recent scholarship in the field. In this essay I summarize a few issues in religious studies today regarding “the sacred” and what possible contribution they might have to Szerszynski's argument and, conversely, how his detailed analysis of the sacred may help this discipline to avoid “philistinism.” The consequences of a universal human nature (from a Darwinian viewpoint) for the concept of the sacred are briefly discussed. In the end, a few suggestions are provided for the ongoing dialogue of science, technology, and religion.